Pendidikan dalam Perspektif Hadis (Suatu Kajian Tematik dalam Bulûgh Al-Marâm) - Abdul Majid Khon (DAYAH: Journal of Islamic Education, 2021)
The hadiths about education in the book Bulûgh Al-Marâm are entirely found and can fulfill the themes of education today, even though this book is characterized by the law of Fiqh (Fiqhul Hadith). There are 17 hadiths or 1.06% of the total 1596 hadiths with the essential word education (ta'lîm). Educational themes that can be fulfilled are; science components, educators, students, educational materials, learning strategies, and teacher salaries. The hadiths found to discuss the importance of useful knowledge. The prophet in Hadith as in the Quran QS. Thaha / 20: 114 only ordered to pray for more knowledge, not ordered to ask for another. The role of educators as servants of students, namely mediators and facilitators. Educators must always learn and have a democratic attitude. Successful students are those who need knowledge and can develop their talents. Teaching material prioritizes ethics or manners and prayer as the practice of knowledge. Teachers may receive honoraria and even have the right to receive an honorarium if the student's condition is worthy of being charged.